Using gold nanoparticles to detect single-nucleotide polymorphisms: toward liquid biopsy - Iglesias, María Sanromán; Grzelczak, Marek (Beilstein Journal of Nanotechnology, 2020)
The possibility of detecting genetic mutations rapidly in physiological media through liquid biopsy has attracted the attention within the materials science community. The physical properties of nanoparticles combined with robust transduction methods ensure an improved sensitivity and specificity of a given assay and its implementation into point-of-care devices for common use. Covering the last twenty years, this review gives an overview of the state-of-the-art of the research on the use of gold nanoparticles in the development of colorimetric biosensors for the detection of single-nucleotide polymorphism as cancer biomarker. We discuss the main mechanisms of the assays that either are assisted by DNA-based molecular machines or by enzymatic reactions, summarize their performance and provide an outlook towards future developments.
Keywords: amplification reactions; biomarkers; colorimetric biosensing; gold nanoparticles; plasmonics; single-point mutation

(untitled) - Ferlay, J.; Soerjomataram, I.; Dikshit, R.; Eser, S.; Mathers, C.; Rebelo, M.; Parkin, D. M.; Forman, D.; Bray, F. (Int. J. Cancer, 2015)

(untitled) - Mandel, P.; Metais, P. (C. R. Seances Soc. Biol. Ses Fil., 1948)

(untitled) - Li, W.; Wang, H.; Zhao, Z.; Gao, H.; Liu, C.; Zhu, L.; Wang, C.; Yang, Y. (Adv. Mater. (Weinheim, Ger.), 2019)

(untitled) - Crowley, E.; Di Nicolantonio, F.; Loupakis, F.; Bardelli, A. (Nat. Rev. Clin. Oncol., 2013)

(untitled) - Bedard, P. L.; Hansen, A. R.; Ratain, M. J.; Siu, L. L. (Nature, 2013)

(untitled) - Sozzi, G.; Conte, D.; Leon, M.; Cirincione, R.; Roz, L.; Ratcliffe, C.; Roz, E.; Cirenei, N.; Bellomi, M.; Pelosi, G.; Pierotti, M. A.; Pastorino, U. (J. Clin. Oncol., 2003)

(untitled) - Kim, K.; Shin, D. G.; Park, M. K.; Baik, S. H.; Kim, T. H.; Kim, S.; Lee, S. (Ann. Surg. Treat. Res., 2014)

(untitled) - Chen, X.; Bonnefoi, H.; Diebold-Berger, S.; Lyautey, J.; Lederrey, C.; Faltin-Traub, E.; Stroun, M.; Anker, P. (Clin. Cancer Res., 1999)

(untitled) - Sozzi, G.; Conte, D.; Mariani, L.; Vullo, S. L.; Roz, L.; Lombardo, C.; Pierotti, M. A.; Tavecchio, L. (Cancer Res., 2001)

(untitled) - Madhavan, D.; Wallwiener, M.; Bents, K.; Zucknick, M.; Nees, J.; Schott, S.; Cuk, K.; Riethdorf, S.; Trumpp, A.; Pantel, K.; Sohn, C.; Schneeweiss, A.; et al. (Breast Cancer Res. Treat., 2014)

(untitled) - Frattini, M.; Gallino, G.; Signoroni, S.; Balestra, D.; Lusa, L.; Battaglia, L.; Sozzi, G.; Bertario, L.; Leo, E.; Pilotti, S.; Pierotti, M. A. (Cancer Lett., 2008)

(untitled) - Chan, K. A.; Jiang, P.; Zheng, Y. W.; Liao, G. J.; Sun, H.; Wong, J.; Siu, S. S. N.; Chan, W. C.; Chan, S. L.; Chan, A. T.; Lai, P. B.; Chiu, R. W.; et al. (Clin. Chem., 2013)

(untitled) - Flohr, T.; Schrauder, A.; Cazzaniga, G.; Panzer-Grümayer, R.; van der Velden, V.; Fischer, S.; Stanulla, M.; Basso, G.; Niggli, F. K.; Schäfer, B. W.; Sutton, R.; Koehler, R.; et al. (Leukemia, 2008)

(untitled) - McBride, D. J.; Orpana, A. K.; Sotiriou, C.; Joensuu, H.; Stephens, P. J.; Mudie, L. J.; Hämäläinen, E.; Stebbings, L. A.; Andersson, L. C.; Flanagan, A. M.; Durbecq, V.; Ignatiadis, M.; et al. (Genes, Chromosomes Cancer, 2010)

(untitled) - Shaw, J. A.; Page, K.; Blighe, K.; Hava, N.; Guttery, D.; Ward, B.; Brown, J.; Ruangpratheep, C.; Stebbing, J.; Payne, R.; Palmieri, C.; Cleator, S.; et al. (Genome Res., 2012)

(untitled) - Leary, R. J.; Sausen, M.; Kinde, I.; Papadopoulos, N.; Carpten, J. D.; Craig, D.; O'Shaughnessy, J.; Kinzler, K. W.; Parmigiani, G.; Vogelstein, B.; Diaz, L. A.; Velculescu, V. E. (Sci. Transl. Med., 2012)

(untitled) - Chan, K. C. A.; Jiang, P.; Chan, C. W. M.; Sun, K.; Wong, J.; Hui, E. P.; Chan, S. L.; Chan, W. C.; Hui, D. S. C.; Ng, S. S. M.; Chan, H. L. Y.; Wong, C. S. C.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Diehl, F.; Schmidt, K.; Choti, M. A.; Romans, K.; Goodman, S.; Li, M.; Thornton, K.; Agrawal, N.; Sokoll, L.; Szabo, S. A.; Kinzler, K. W.; Vogelstein, B.; et al. (Nat. Med., 2008)

(untitled) - Dawson, S.-J.; Tsui, D. W. Y.; Murtaza, M.; Biggs, H.; Rueda, O. M.; Chin, S.-F.; Dunning, M. J.; Gale, D.; Forshew, T.; Mahler-Araujo, B.; Rajan, S.; Humphray, S.; et al. (N. Engl. J. Med., 2013)

(untitled) - Heitzer, E.; Ulz, P.; Belic, J.; Gutschi, S.; Quehenberger, F.; Fischereder, K.; Benezeder, T.; Auer, M.; Pischler, C.; Mannweiler, S.; Pichler, M.; Eisner, F.; et al. (Genome Med., 2013)

(untitled) - Karapetis, C. S.; Khambata-Ford, S.; Jonker, D. J.; O'Callaghan, C. J.; Tu, D.; Tebbutt, N. C.; Simes, R. J.; Chalchal, H.; Shapiro, J. D.; Robitaille, S.; Price, T. J.; Shepherd, L.; et al. (N. Engl. J. Med., 2008)

(untitled) - Kuo, Y.-B.; Chen, J.-S.; Fan, C.-W.; Li, Y.-S.; Chan, E.-C. (Clin. Chim. Acta, 2014)

(untitled) - Valtorta, E.; Misale, S.; Sartore-Bianchi, A.; Nagtegaal, I. D.; Paraf, F.; Lauricella, C.; Dimartino, V.; Hobor, S.; Jacobs, B.; Ercolani, C.; Lamba, S.; Scala, E.; et al. (Int. J. Cancer, 2013)

(untitled) - Thierry, A. R.; Mouliere, F.; El Messaoudi, S.; Mollevi, C.; Lopez-Crapez, E.; Rolet, F.; Gillet, B.; Gongora, C.; Dechelotte, P.; Robert, B.; Del Rio, M.; Lamy, P.-J.; et al. (Nat. Med., 2014)

(untitled) - Mohan, S.; Heitzer, E.; Ulz, P.; Lafer, I.; Lax, S.; Auer, M.; Pichler, M.; Gerger, A.; Eisner, F.; Hoefler, G.; Bauernhofer, T.; Geigl, J. B.; et al. (PLoS Genet., 2014)

(untitled) - Misale, S.; Yaeger, R.; Hobor, S.; Scala, E.; Janakiraman, M.; Liska, D.; Valtorta, E.; Schiavo, R.; Buscarino, M.; Siravegna, G.; Bencardino, K.; Cercek, A.; et al. (Nature, 2012)

(untitled) - Lecomte, T.; Berger, A.; Zinzindohoué, F.; Micard, S.; Landi, B.; Blons, H.; Beaune, P.; Cugnenc, P.-H.; Laurent-Puig, P. (Int. J. Cancer, 2002)

(untitled) - Spindler, K.-L. G.; Pallisgaard, N.; Vogelius, I.; Jakobsen, A. (Clin. Cancer Res., 2012)

(untitled) - Schmitt, M. W.; Kennedy, S. R.; Salk, J. J.; Fox, E. J.; Hiatt, J. B.; Loeb, L. A. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Alix-Panabières, C.; Pantel, K. (Nat. Rev. Cancer, 2014)

(untitled) - Taylor, D. D.; Gercel-Taylor, C. (Semin. Immunopathol., 2011)

(untitled) - Kosaka, N.; Iguchi, H.; Ochiya, T. (Cancer Sci., 2010)

(untitled) - Luna Coronell, J. A.; Syed, P.; Sergelen, K.; Gyurján, I.; Weinhäusel, A. (J. Proteomics, 2012)

(untitled) - Diaz, L. A., Jr; Bardelli, A. (J. Clin. Oncol., 2014)

(untitled) - Aarthy, R.; Mani, S.; Velusami, S.; Sundarsingh, S.; Rajkumar, T. (Mol. Diagn. Ther., 2015)

(untitled) - Chaudhuri, A. A.; Binkley, M. S.; Osmundson, E. C.; Alizadeh, A. A.; Diehn, M. (Semin. Radiat. Oncol., 2015)

(untitled) - Ignatiadis, M.; Lee, M.; Jeffrey, S. S. (Clin. Cancer Res., 2015)

(untitled) - Polivka, J., Jr; Pesta, M.; Janku, F. (Expert Rev. Mol. Diagn., 2015)

(untitled) - Newman, A. M.; Bratman, S. V.; To, J.; Wynne, J. F.; Eclov, N. C. W.; Modlin, L. A.; Liu, C. L.; Neal, J. W.; Wakelee, H. A.; Merritt, R. E.; Shrager, J. B.; Loo, B. W.; et al. (Nat. Med., 2014)

(untitled) - Fan, X.; White, I. M.; Shopova, S. I.; Zhu, H.; Suter, J. D.; Sun, Y. (Anal. Chim. Acta, 2008)

(untitled) - Jahr, S.; Hentze, H.; Englisch, S.; Hardt, D.; Fackelmayer, F. O.; Hesch, R. D.; Knippers, R. (Cancer Res., 2001)

(untitled) - Mouliere, F.; Robert, B.; Arnau Peyrotte, E.; Del Rio, M.; Ychou, M.; Molina, F.; Gongora, C.; Thierry, A. R. (PLoS One, 2011)

(untitled) - Siravegna, G.; Bardelli, A. (Mol. Oncol., 2016)

(untitled) - Schwarzenbach, H.; Hoon, D. S. B.; Pantel, K. (Nat. Rev. Cancer, 2011)

(untitled) - Wan, J. C. M.; Massie, C.; Garcia-Corbacho, J.; Mouliere, F.; Brenton, J. D.; Caldas, C.; Pacey, S.; Baird, R.; Rosenfeld, N. (Nat. Rev. Cancer, 2017)

(untitled) - Diehl, F.; Li, M.; Dressman, D.; He, Y.; Shen, D.; Szabo, S.; Diaz, L. A.; Goodman, S. N.; David, K. A.; Juhl, H.; Kinzler, K. W.; Vogelstein, B. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Holdhoff, M.; Schmidt, K.; Donehower, R.; Diaz, L. A. (J. Natl. Cancer Inst., 2009)

(untitled) - Brookes, A. J. (Gene, 1999)

(untitled) - Kim, S.; Misra, A. (Annu. Rev. Biomed. Eng., 2007)

(untitled) - Collins, F. S.; Guyer, M. S.; Chakravarti, A. (Science, 1997)

(untitled) - Camp, K. M.; Trujillo, E. (J. Acad. Nutr. Diet., 2014)

(untitled) - Halushka, M. K.; Fan, J.-B.; Bentley, K.; Hsie, L.; Shen, N.; Weder, A.; Cooper, R.; Lipshutz, R.; Chakravarti, A. (Nat. Genet., 1999)

Single Nucleotide Polymorphisms - Komar, A. A. (Humana Press, 2009)

(untitled) - Sobrino, B.; Brión, M.; Carracedo, A. (Forensic Sci. Int., 2005)

(untitled) - Kwok, P.-Y. (Annu. Rev. Genomics Hum. Genet., 2001)

(untitled) - Forshew, T.; Murtaza, M.; Parkinson, C.; Gale, D.; Tsui, D. W. Y.; Kaper, F.; Dawson, S.-J.; Piskorz, A. M.; Jimenez-Linan, M.; Bentley, D.; Hadfield, J.; May, A. P.; et al. (Sci. Transl. Med., 2012)

(untitled) - Castells, A.; Puig, P.; Móra, J.; Boadas, J.; Boix, L.; Urgell, E.; Solé, M.; Capellà, G.; Lluís, F.; Fernández-Cruz, L.; Navarro, S.; Farré, A. (J. Clin. Oncol., 1999)

(untitled) - Nygaard, A. D.; Garm Spindler, K.-L.; Pallisgaard, N.; Andersen, R. F.; Jakobsen, A. (Lung Cancer, 2013)

(untitled) - Zhan, C.; Chen, X.-J.; Yi, J.; Li, J.-F.; Wu, D.-Y.; Tian, Z.-Q. (Nat. Rev. Chem., 2018)

(untitled) - Elghanian, R.; Storhoff, J. J.; Mucic, R. C.; Letsinger, R. L.; Mirkin, C. A. (Science, 1997)

(untitled) - Storhoff, J. J.; Elghanian, R.; Mucic, R. C.; Mirkin, C. A.; Letsinger, R. L. (J. Am. Chem. Soc., 1998)

(untitled) - Sato, K.; Hosokawa, K.; Maeda, M. (J. Am. Chem. Soc., 2003)

(untitled) - Li, H.; Rothberg, L. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Chen, J.; Tang, L.; Chu, X.; Jiang, J. (Analyst, 2017)

(untitled) - Zhu, X.; Liu, Y.; Yang, J.; Liang, Z.; Li, G. (Biosens. Bioelectron., 2010)

(untitled) - Lee, H.; Kang, T.; Yoon, K.-A.; Lee, S. Y.; Joo, S.-W.; Lee, K. (Biosens. Bioelectron., 2010)

(untitled) - Zhou, W.; Ren, J.; Zhu, J.; Zhou, Z.; Dong, S. (Talanta, 2016)

(untitled) - Charrier, A.; Candoni, N.; Liachenko, N.; Thibaudau, F. (Biosens. Bioelectron., 2007)

(untitled) - Duan, R.; Wang, B.; Hong, F.; Zhang, T.; Jia, Y.; Huang, J.; Hakeem, A.; Liu, N.; Lou, X.; Xia, F. (Nanoscale, 2015)

(untitled) - McKenzie, F.; Faulds, K.; Graham, D. (Small, 2007)

(untitled) - Veigas, B.; Machado, D.; Perdigão, J.; Portugal, I.; Couto, I.; Viveiros, M.; Baptista, P. V. (Nanotechnology, 2010)

(untitled) - Yun, W.; Jiang, J.; Cai, D.; Zhao, P.; Liao, J.; Sang, G. (Biosens. Bioelectron., 2016)

(untitled) - Valentini, P.; Fiammengo, R.; Sabella, S.; Gariboldi, M.; Maiorano, G.; Cingolani, R.; Pompa, P. P. (ACS Nano, 2013)

(untitled) - Su, X.; Kanjanawarut, R. (ACS Nano, 2009)

(untitled) - Murphy, D.; O'Brien, P.; Redmond, G. (Analyst, 2004)

(untitled) - Bao, Y. P.; Huber, M.; Wei, T.-F.; Marla, S. S.; Storhoff, J. J.; Müller, U. R. (Nucleic Acids Res., 2005)

(untitled) - He, Y.; Zeng, K.; Gurung, A. S.; Baloda, M.; Xu, H.; Zhang, X.; Liu, G. (Anal. Chem. (Washington, DC, U. S.), 2010)

(untitled) - Quan, K.; Huang, J.; Yang, X.; Yang, Y.; Ying, L.; Wang, H.; Wang, K. (Analyst, 2015)

(untitled) - Nam, J.-M.; Stoeva, S. I.; Mirkin, C. A. (J. Am. Chem. Soc., 2004)

(untitled) - Taton, T. A.; Mirkin, C. A.; Letsinger, R. L. (Science, 2000)

(untitled) - Park, C.; Song, Y.; Jang, K.; Choi, C.-H.; Na, S. (Sens. Actuators, B, 2018)

(untitled) - Xu, C.; Lan, L.; Yao, Y.; Ping, J.; Li, Y.; Ying, Y. (Sens. Actuators, B, 2018)

(untitled) - Song, T.; Xiao, S.; Yao, D.; Huang, F.; Hu, M.; Liang, H. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Ma, C.; Wang, W.; Mulchandani, A.; Shi, C. (Anal. Biochem., 2014)

(untitled) - Guo, L.; Xu, Y.; Ferhan, A. R.; Chen, G.; Kim, D.-H. (J. Am. Chem. Soc., 2013)

(untitled) - Fan, A.; Cai, S.; Cao, Z.; Lau, C.; Lu, J. (Analyst, 2010)

(untitled) - Shawky, S. M.; Bald, D.; Azzazy, H. M. E. (Clin. Biochem., 2010)

(untitled) - Hu, Y.; Zhang, L.; Zhang, Y.; Wang, B.; Wang, Y.; Fan, Q.; Huang, W.; Wang, L. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Sedighi, A.; Li, P. C. H. (Anal. Biochem., 2014)

(untitled) - Fang, W.-F.; Chen, W.-J.; Yang, J.-T. (Sens. Actuators, B, 2014)

(untitled) - Kanjanawarut, R.; Su, X. (Anal. Chem. (Washington, DC, U. S.), 2009)

(untitled) - Lee, H.; Kim, A.; Ahn, I.-S.; Joo, S.-W.; Lee, S. Y.; Yoon, K.-A.; Lee, K. (Chem. Commun., 2011)

(untitled) - Kato, D.; Oishi, M. (ACS Nano, 2014)

(untitled) - Sanromán-Iglesias, M.; Lawrie, C. H.; Schäfer, T.; Grzelczak, M.; Liz-Marzán, L. M. (ACS Sens., 2016)

(untitled) - Sanromán-Iglesias, M.; Lawrie, C. H.; Liz-Marzán, L. M.; Grzelczak, M. (Bioconjugate Chem., 2017)

(untitled) - Sanromán-Iglesias, M.; Lawrie, C. H.; Liz-Marzán, L. M.; Grzelczak, M. (ACS Appl. Nano Mater., 2018)

(untitled) - Piao, J.; Zhao, Q.; Zhou, D.; Peng, W.; Gao, W.; Chen, M.; Shu, G.; Gong, X.; Chang, J. (Anal. Chim. Acta, 2019)

(untitled) - Jian, J.-W.; Huang, C.-C. (Chem. – Eur. J., 2011)

(untitled) - Jung, Y. L.; Jung, C.; Parab, H.; Cho, D.-Y.; Park, H. G. (ChemBioChem, 2011)

(untitled) - Li, J.; Chu, X.; Liu, Y.; Jiang, J.-H.; He, Z.; Zhang, Z.; Shen, G.; Yu, R.-Q. (Nucleic Acids Res., 2005)

(untitled) - Xu, W.; Xue, X.; Li, T.; Zeng, H.; Liu, X. (Angew. Chem., Int. Ed., 2009)

(untitled) - He, Y.; Zeng, K.; Zhang, S.; Gurung, A. S.; Baloda, M.; Zhang, X.; Liu, G. (Biosens. Bioelectron., 2012)

(untitled) - Chen, Y.-T.; Hsu, C.-L.; Hou, S.-Y. (Anal. Biochem., 2008)

(untitled) - Wang, Q.; Li, R.-D.; Yin, B.-C.; Ye, B.-C. (Analyst, 2015)

(untitled) - Zou, B.; Cao, X.; Wu, H.; Song, Q.; Wang, J.; Kajiyama, T.; Kambara, H.; Zhou, G. (Biosens. Bioelectron., 2015)

(untitled) - Wu, S.; Liang, P.; Yu, H.; Xu, X.; Liu, Y.; Lou, X.; Xiao, Y. (Anal. Chem. (Washington, DC, U. S.), 2014)

(untitled) - Li, R.-D.; Yin, B.-C.; Ye, B.-C. (Biosens. Bioelectron., 2016)

(untitled) - Cui, L.; Ke, G.; Zhang, W. Y.; Yang, C. J. (Biosens. Bioelectron., 2011)

(untitled) - Li, J.; Song, S.; Liu, X.; Wang, L.; Pan, D.; Huang, Q.; Zhao, Y.; Fan, C. (Adv. Mater. (Weinheim, Ger.), 2008)

(untitled) - Xu, W.; Xie, X.; Li, D.; Yang, Z.; Li, T.; Liu, X. (Small, 2012)

(untitled) - Jung, C.; Chung, J. W.; Kim, U. O.; Kim, M. H.; Park, H. G. (Biosens. Bioelectron., 2011)

(untitled) - Akiyama, Y.; Shikagawa, H.; Kanayama, N.; Takarada, T.; Maeda, M. (Chem. – Eur. J., 2014)

(untitled) - Liu, M.; Yuan, M.; Lou, X.; Mao, H.; Zheng, D.; Zou, R.; Zou, N.; Tang, X.; Zhao, J. (Biosens. Bioelectron., 2011)

(untitled) - Shen, W.; Deng, H.; Gao, Z. (J. Am. Chem. Soc., 2012)

(untitled) - Wang, X.; Zou, M.; Huang, H.; Ren, Y.; Li, L.; Yang, X.; Li, N. (Biosens. Bioelectron., 2013)

(untitled) - Han, J.; Tan, M.; Sudheendra, L.; Weiss, R. H.; Kennedy, I. M. (Nano Res., 2014)

(untitled) - Kim, H.; Kang, S.; Park, K. S.; Park, H. G. (Sens. Actuators, B, 2018)

(untitled) - Shan, Y.; Xu, J.-J.; Chen, H.-Y. (Chem. Commun., 2009)

(untitled) - Ren, X.; Xue, Q.; Wen, L.; Li, X.; Wang, H. (Anal. Chim. Acta, 2019)

(untitled) - Zhu, D.; Lu, B.; Zhu, Y.; Ma, Z.; Wei, Y.; Su, S.; Wang, L.; Song, S.; Zhu, Y.; Wang, L.; Chao, J. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Zhou, H.; Liu, J.; Xu, J.-J.; Chen, H.-Y. (Chem. Commun., 2011)

(untitled) - Zeng, Y.-p.; Zhu, G.; Yang, X.-y.; Cao, J.; Jing, Z.-l.; Zhang, C.-y. (Chem. Commun., 2014)

(untitled) - Yang, D.; Guo, Z.; Wang, J.; Jin, Y.; Mei, Q.; Miao, P. (Part. Part. Syst. Charact., 2019)

(untitled) - Li, N.; Li, R.; Li, Z.; Yang, Y.; Wang, G.; Gu, Z. (Sens. Actuators, B, 2019)

(untitled) - Wang, Y.; Howes, P. D.; Kim, E.; Spicer, C. D.; Thomas, M. R.; Lin, Y.; Crowder, S. W.; Pence, I. J.; Stevens, M. M. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Roy, S.; Soh, J. H.; Ying, J. Y. (Biosens. Bioelectron., 2016)

(untitled) - Ihara, T.; Tanaka, S.; Chikaura, Y.; Jyo, A. (Nucleic Acids Res., 2004)

(untitled) - Sato, Y.; Sato, K.; Hosokawa, K.; Maeda, M. (Anal. Biochem., 2006)

(untitled) - Fong, K. E.; Yung, L.-Y. L. (RSC Adv., 2013)

(untitled) - Ma, X.; Truong, P. L.; Anh, N. H.; Sim, S. J. (Biosens. Bioelectron., 2015)

(untitled) - Chakrabarti, R.; Klibanov, A. M. (J. Am. Chem. Soc., 2003)

(untitled) - Yurke, B.; Turberfield, A. J.; Mills, A. P.; Simmel, F. C.; Neumann, J. L. (Nature, 2000)

(untitled) - Dirks, R. M.; Pierce, N. A. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Bois, J. S.; Venkataraman, S.; Choi, H. M. T.; Spakowitz, A. J.; Wang, Z.-G.; Pierce, N. A. (Nucleic Acids Res., 2005)

(untitled) - Dai, W.; Zhang, J.; Meng, X.; He, J.; Zhang, K.; Cao, Y.; Wang, D.; Dong, H.; Zhang, X. (Theranostics, 2018)

(untitled) - Reid, M. S.; Le, X. C.; Zhang, H. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhao, Y.; Chen, F.; Li, Q.; Wang, L.; Fan, C. (Chem. Rev., 2015)

(untitled) - Wang, L.; Zhu, Y.; Xu, L.; Chen, W.; Kuang, H.; Liu, L.; Agarwal, A.; Xu, C.; Kotov, N. A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Grzelczak, M.; Liz-Marzán, L. M.; Klajn, R. (Chem. Soc. Rev., 2019)

(untitled) - Caracciolo, G.; Safavi-Sohi, R.; Malekzadeh, R.; Poustchi, H.; Vasighi, M.; Zenezini Chiozzi, R.; Capriotti, A. L.; Laganà, A.; Hajipour, M.; Di Domenico, M.; Di Carlo, A.; Caputo, D.; et al. (Nanoscale Horiz., 2019)

(untitled) - Cohen, J. D.; Li, L.; Wang, Y.; Thoburn, C.; Afsari, B.; Danilova, L.; Douville, C.; Javed, A. A.; Wong, F.; Mattox, A.; Hruban, R. H.; Wolfgang, C. L.; et al. (Science, 2018)

(untitled) - Banerjee, R.; Jaiswal, A. (Analyst, 2018)

(untitled) - Huang, X.; Aguilar, Z. P.; Xu, H.; Lai, W.; Xiong, Y. (Biosens. Bioelectron., 2016)

(untitled) - Quesada-González, D.; Merkoçi, A. (Biosens. Bioelectron., 2015)

(untitled) - Bahadır, E. B.; Sezgintürk, M. K. (TrAC, Trends Anal. Chem., 2016)

(untitled) - del Pino, P.; Pelaz, B.; Zhang, Q.; Maffre, P.; Nienhaus, G. U.; Parak, W. J. (Mater. Horiz., 2014)